2005
DOI: 10.1007/s10592-004-7830-x
|View full text |Cite
|
Sign up to set email alerts
|

Increased inbreeding and inter-species gene flow in remnant populations of the rare Eucalyptus benthamii

Abstract: Eucalyptus benthamiiMaiden & Cambage is a forest tree of interest for conservation and plantation forestry. It is vulnerable to extinction, occurring on the alluvial floodplains of the Nepean River and its tributaries, south-west of Sydney, Australia. These floodplains were largely cleared of native vegetation for agriculture by the mid-1800s. Flooding of the Cox Valley for Sydney's water supply further decreased the species distribution. The species is now confined to one population of approximately 6500 tree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
1
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 25 publications
5
46
1
2
Order By: Relevance
“…(HIGA;PEREIRA, 2003). Essa espécie é considerada vulnerável ao desaparecimento na região de ocorrência natural, correspondente ao curso do Rio Nepean, a oeste de Sydney, Austrália (BUTCHER et al, 2005).…”
Section: Introductionunclassified
“…(HIGA;PEREIRA, 2003). Essa espécie é considerada vulnerável ao desaparecimento na região de ocorrência natural, correspondente ao curso do Rio Nepean, a oeste de Sydney, Austrália (BUTCHER et al, 2005).…”
Section: Introductionunclassified
“…However, the absence of such a relationship is common in eucalypts (reviewed by Butcher et al 2005), and this was the case for E. cordata. Allelic richness is a highly sensitive genetic diversity parameter and is influenced by the loss of rare alleles following bottlenecks in population size (Maruyama and Fuerst 1985).…”
Section: Discussionmentioning
confidence: 99%
“…Mating system studies have shown that increased within-plant foraging and reduced local mate availability appears to affect pollen quality in fragmented populations of many eucalypts and other Myrtaceae, resulting in reduced seed set (Krauss et al, 2007;Yates et al, 2007b;Gauli et al, 2014), while late-acting selfincompatibility mechanisms may have prevented outcrossing rates from being significantly affected by fragmentation in many species (Ottewell et al, 2009;Gauli et al, 2014;Breed et al, 2015), but not all (Butcher et al, 2005;Mimura et al, 2009;Breed et al, 2015). Despite changes in pollen quality, the level of pollination and pollinator abundance was unchanged in Calothamnus quadrifidus (Yates et al, 2007a), while honeybees have increased (González-Varo et al, 2009) or decreased (Hingston et al, 2004) pollination rates in some species of Myrtaceae.…”
Section: Introductionmentioning
confidence: 99%